Cerebrospinal fluid transthyretin: aging and late onset Alzheimer's disease. Issue 4 (1st October 1997) - Serot, J-M; Christmann, D; Dubost, T; Couturier, M
Abstract : The deposition of insoluble β-amyloid protein fibrils is probably the central event in the pathogenesis of Alzheimer's disease. Cerebrospinal fluid inhibits this fibril formation, likely by the intervention of one or several proteins binding to soluble β-amyloid protein. In vitro, transthyretin (TTR), a CSF protein, impedes amyloid fibrillogenesis. Lowered concentrations of CSFTTR could therefore be associated with Alzheimer's disease. Concentrations of TTR in CSF samples from 149 consecutive patients were assayed, using a kinetic nephelemetric method. These concentrations were correlated positively with age, but were significantly lower in patients with Alzheimer's disease. These data raise the possibility that amyloid fibril formation could be promoted in patients with late onset Alzheimer's disease by the lack of sufficient concentrations of TTR.